The “Caravana pelo Direito à Habitação”: Towards a new movement for housing in Portugal? - Falanga, Roberto (2019)
The Caravana pelo Direito à Habitação travelled across Portugal together with local groups and associations to collect information on and give visibility to housing needs, while aiming to create new networks and influence the national political agenda. This conversation brings together seven scholar-activists that participated in the Caravana, who reflect upon the Caravana and contemporary struggles on the right to housing in Portugal. The conversation sheds light on some contentious issues that are presented through a selection of relevant excerpts, which cover personal identities as scholar-activists; contexts shaping contemporary housing struggles; and the relation of the Caravana to the the politics of housing in Portugal.